Food knowledge and psychological state predict adherence to a gluten‐free diet in a survey of 5310 Australians and New Zealanders with coeliac disease. Issue 1 (7th May 2018) - Halmos, E. P.; Deng, M.; Knowles, S. R.; Sainsbury, K.; Mullan, B.; Tye‐Din, J. A.
Summary: Background: A gluten‐free diet treats coeliac disease, but its efficacy depends on strict adherence. A variety of patient factors may influence adherence but have not been well described at a population level. Aim: To comprehensively assess the patient factors that influence gluten‐free diet adherence in patients with coeliac disease. Methods: Patients with coeliac disease completed an online survey comprising the validated Celiac Dietary Adherence Test in addition to data on demographics, details of diagnosis and management and assessment of diet knowledge, quality of life and psychological distress. Survey data were analysed for predictors of adherence and quality of life. Results: Of 7393 responses, 5310 completed the Celiac Dietary Adherence Test and 3230 (61%) were adherent to a gluten‐free diet. Multivariate regression showed older age, being male, symptoms after gluten ingestion, better food knowledge and lower risk of psychological distress were independent predictors of adherence (each P  ≤ 0.008). Additionally, dietary adherence was associated with better quality of life ( P  < 0.001; multiple regression). Respondents who considered themselves to have poor food knowledge were more likely to incorrectly identify gluten‐free foods, but could still recognise gluten‐containing foods, suggesting that poor knowledge may lead to over‐restriction of diet. Conclusions: Poor knowledge of a gluten‐free diet and psychological wellbeing were independent modifiable risk factors for inadequate adherence to a gluten‐free diet in patients with coeliac disease. Involvement of both a dietitian and mental health care professional, in the presence of psychological distress, is likely to be necessary to improve adherence and health outcomes. Abstract : Linked Content This article is linked to Swift and Woodward paper. To view this article visithttps://doi.org/10.1111/apt.14830 .